2010
DOI: 10.1098/rsbl.2010.0126
|View full text |Cite
|
Sign up to set email alerts
|

Proximate determinants of telomere length in sand lizards ( Lacerta agilis )

Abstract: Telomeres are repeat sequences of non-coding DNA that cap the ends of chromosomes and contribute to their stability and the genomic integrity of cells. In evolutionary ecology, the main research target regarding these genomic structures has been their role in ageing and as a potential index of age. However, research on humans shows that a number of traits contribute to among-individual differences in telomere length, in particular traits enhancing cell division and genetic erosion, such as levels of free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 19 publications
5
48
0
Order By: Relevance
“…TL is measured in a variety of ways in the ecological literature. The most common methods are the Southern blot-derived telomere restriction fragment (TRF) assay [911], smaller windows of the TRF smear [12], and quantitative PCR [8,13,14]. Here we compare the effects of age, sex, and colony on telomere length as estimated by each of those methods.…”
Section: Introductionmentioning
confidence: 99%
“…TL is measured in a variety of ways in the ecological literature. The most common methods are the Southern blot-derived telomere restriction fragment (TRF) assay [911], smaller windows of the TRF smear [12], and quantitative PCR [8,13,14]. Here we compare the effects of age, sex, and colony on telomere length as estimated by each of those methods.…”
Section: Introductionmentioning
confidence: 99%
“…We show elsewhere that in sand lizards ( Lacerta agilis ), there are sex-specific effects relating to telomere length (TL), such as stress-tolerance from predation [4] and positive selection in the wild relating to increased lifespan and lifetime reproductive success (stronger in females; 4; oral report at the Swedish Telomere and Telomerase Network Annual Meeting, Sven Lovén Centre, May 2010; Olsson et al submitted). However, the genetic architecture and epigenetic aspects of the underlying processes determining telomere length have not been addressed, which makes it difficult to assess the evolutionary implications of selection patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The Maier et al (2008) study, discussed earlier, showed that human cell replicative capacity is dependent on height when the donor is male, but not when female. Moreover, large male dunlins (Calidris alpine) and sand lizards (Lacerta agilis) have shorter telomeres than small males, but size does not affect female telomere length, despite them being the larger sex (Pauliny et al, 2006;Olsson et al, 2010;respectively). Nevertheless, most species with no sex differences in telomere length or shortening do still show an age-related decline in telomere length (Table 1), which we might not expect if telomeres were fully maintained by telomerase.…”
Section: Bigger Not Always Better?mentioning
confidence: 99%